Estudio de técnicas instrumentales para análisis de residuos de disparo inorgánicos. - Guevara Guevara, Cyntia Magali (2025)
The project consists of the creation of an updated bibliographic reference that, through the application of appropriate scientific methodologies, allows an explanation of the different types of shot residues, the instrumental techniques used for its analysis, and the methods of analysis of inorganic shot residues, which will allow to establish the suitability of each method for sample treatment and the results obtained. Furthermore, this study aims to develop a reliable and current bibliographic source regarding the instrumental techniques used for gunshot residue analysis. The research follows a mixed approach, which best meets the requirements of the study. This approach includes resources such as a comprehensive bibliographic review, surveys, interviews, and various methodological processes. The primary objective is establishing comparative parameters for selecting an instrumental technique for analyzing inorganic gunshot residues in Ecuador. The preferred methods are non-destructive or minimally invasive during the collection, treatment, and analysis of samples, thus ensuring the preservation of evidence.